LELANG JABATAN LURAH DALAM PERSPEKTIF PELAYANAN PUBLIK DI DKI JAKARTA - MA, Firman (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2016)
This study about the impact of the post of head of village (lurah) auction to service at the Communities in Jakarta. Auction office of head of village (lurah) and other structural hierarchy, led by the Jakarta administration. The birth of this policy is to maximize the public service to the community in general. This is because the issue of community dissatisfaction with basic services. This makes the bureaucratic system in terms of public services is stagnant at this basic services. Moreover, the reform of the bureaucracy and far Agenda collusive behavior, corruption and nepotism which has not made such a significant. The birth of the auction office innovation is expected to have a significant impact.